GENERATIONS IN BAYESIAN NETWORKS - Litvinenko, Alexander; Litvinenko, Natalya; Mamyrbayev, Orken; Shayakhmetova, Assem (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2019)
This paper focuses on the study of some aspects of the theory of oriented graphs in Bayesian networks. In some papers on the theory of Bayesian networks, the concept of “Generation of vertices” denotes a certain set of vertices with many parents belonging to previous generations. Terminology for this concept, in our opinion, has not yet fully developed. The concept of “Generation” in some cases makes it easier to solve some problems in Bayesian networks and to build simpler algorithms. In this paper we will consider the well-known example “Asia”, described in many articles and books, as well as in the technical documentation for various toolboxes. For the construction of this example, we have used evaluation versions of AgenaRisk.